Develoment and validation of HPLC-DAD methods for quantification of phenytoin and glycoprotein inhibitors (Elacridar and Tariquidar) in plasma - Stefany Huaynasi Aguirre (2020)
Two simple, rapid, selective and sensitive bioanalytical methods were developed and validated by HPLC-DAD, one for the determination and quantification of phenytoin, and another for inhibitors of P-glycoprotein (tariquidar and elacridar) using 0.2ml of plasma. The analytes were separated using Chromolith® Performance RP-18 100 - 4.6 mm column, with a mobile phase composed of ACN: 10mM acetate buffer pH = 5.2 (27.5: 72.5) for phenytoin and its EI, forthe determination of tariquidar , elacridar and its EI ACN: MeOH: 10mM acetate buffer pH = 5.2 (30:50:20) was used, in both methods a flow of 1mL / min, temperature of 25 ± 1 ° C, a complement of slingshot of 210nm The methods proved to be linear and sensitive, the phenytoin method in the range of 100 to 50,000 ng / mL (LC = 36.98 ng / mL, LD = 98.79 ng / mL) and inhibitors of 100 to 20,000 ng / mL (LC = 36.98 ng / mL, LD = 98.79 ng / mL), also showedto be accurate (% CV <15), reproducible and accurate. The recovery was greater than 97% (phenytoin) and 93% (inhibitors), both methods presented stability in freezing and thawing cycles, short-term stability (5h and 24h) and long-term stability for up to 3 months at -20 ° C. The bioanalytical methods developed and validated may be used to evaluate the effect on the pharmacokinetics and bioavailability of the co-administration of tariquidar and elacridar with phenytoin.